Experimental investigation of snake robot locomotion in planar space - Billah, Md. Masum; Khan, Md. Raisuddin; Shafie, Amir Akramin (2013)
An experimental investigation of a snake robot has been discussed and analyzed in this paper. This experimental investigation involves elementary possessions of the angular velocity of a snake robot by carrying out serpentine locomotion. This is a preparatory experimental work to go for the real snake experiment involving snake locomotion in future. To investigate snake locomotion by capturing image and then retrieve data by image processing or by using 3D motion analysis to capture data are not precise solution. Therefore, rate gyro and accelerometer are used in this research to retrieve the angular velocity of the snake robot motion. Finally, this work shows a experimental locomotion data to proceed this work for the further investigation of the snake motion.